Pendidikan Kesehatan Dalam Pengendalian Infeksi Pada Pasien Dan Keluarga Pasien di Rumah Sakit Umum Dewi Sartika - Erni Erni; Muhammad Al Rajab; Rania Fatrizza Pritami; Sultan Andilah; Marheni Fadilah Harun; Fitri Kurniawati; Noviani Munsir; Harni Harni; Dian Rosmala Lestari; Venia Oktafiani; Ditra Yuniar; Pemmi Fadilla Tosepu (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
The infection that occurs in a hospital setting, also known as nosocomial infection or Hospital Acquired Infections (HAIs), is a serious issue in public health. This research aims to evaluate the impact of health education in controlling infections among patients and their families at Dewi Sartika General Hospital. Involving 30 respondents, the knowledge and attitudes of the respondents regarding infection control were observed before and after the administration of health education. The results of data analysis showed a significant difference in respondents' knowledge before and after health education, with a p-value of 0.000 and a t-value of -18.886. Before health education, the average knowledge of respondents was 19.77, significantly increasing to 25.70 after health education. This indicates that health education is effective in improving respondents' knowledge regarding cleanliness practices and infection prevention. Furthermore, in the attitude variable, the results showed a significant difference with a p-value of 0.000 and a t-value of -12.042. Respondents' attitudes toward infection control experienced a positive increase after the administration of health education. Before health education, the average attitude of respondents was 20.00, and it increased to 26.50 after the intervention. Therefore, it can be concluded that health education not only influences knowledge but also stimulates positive changes in respondents' attitudes towards infection control. These findings provide support for the integration of health education as an effective strategy in efforts to control infections in the hospital environment.